Farklı Türden Kontak Lenslerin Ultraviyole Işık Geçirgenliğinin Ölçülmesi - Barlık, Ahmet; Ateş, Gonca (Fırat Üniversitesi, 2023)
Ultraviyole radyasyonun farklı oküler dokular üzerinde zararlı etkilerini gösteren bilimsel kanıtlar üreticileri UV bloke edici monomerleri kontak lenslere dâhil etmeye yönlendirmiştir. Bu araştırmada, kontak lenslerin spektral ve optik özellikleri ultraviyole ve görünür ışık dalga boyu aralıklarında JASCO V-730 UV/Vis spektrofotometre cihazı kullanılarak analiz edildi Elde edilen sonuçlar incelenen kontak lens örneklerinde insan gözünün en duyarlı olduğu dalga boyu (550 nm) aralığında ışık geçirgenliğinin %70’nin üzerinde olduğunu ve maksimum değere %72,98 olarak B kontak lensin sahip olduğunu gösterdi. En büyük kesme kenarı dalga boyu değeri A kontak lensinde 376 nm olarak elde edildi.550 nm’de soğurma spektrumlarının ise 0.12 altında olduğu bulundu. Görme kalitesi açısından görünür ışık geçirgenliğinin yüksek olması, ultraviyole ışık geçirgenliğinin minimum olması beklenir. Ultraviyole korumalı monomer içeren ve içermeyen kontak lenslerden A lensinin UV-B dalga boyu bölgesini geçirmediği, B lensinin ise UV-A ve UV-B dalga boylarını geçirdiği görüldü. Bu sonuç A lensinin korumasının daha yüksek olduğunu gösterdi. Fokometre ile alınan UV geçirgenlikleri A lensinde %45, B lensinde %91 olarak görülmektedir. UV/Vis spektrofotometre ile fokometreden alınan sonuçlar birbirini destekledi. Sonuçlar, görme gereçlerinde UV korumalı monomer içerikli kontak lenslerin önemini ortaya çıkararak, tam korumalı kontak lenslerin geliştirilmesini ve seçilmesini sağlayarak literatüre katkı sağlayacaktır.

Scientific evidence showing the harmful effects of ultraviolet radiation on different ocular tissues has led manufacturers to incorporate UV-blocking monomers into contact lenses. In this study, the spectral and optical properties of contact lenses were analyzed in the ultraviolet and visible light wavelength ranges using the Jasco V-730 UV/VIS spectrophotometer device. The results obtained showed that in the lens samples examined, the light transmittance in the wavelength (550nm) range to which the human eye is most sensitive is over 70% and the maximum value is 72.98% in B contact lenses. The largest cutting edge wavelength value was obtained in the A contact lens as 376 nm. At 550 nm, the absorption spectra were found to be below 0.12. In terms of visual quality, visible light transmittance is expected to be high and ultraviolet light transmittance is expected to be minimal. The degree of damage caused by the amount of ultraviolet light absorption increases. Among the contact lenses with and without ultraviolet-protected monomers, lens A did not transmit the UV-B wavelength region, while lens B transmitted UV-A and UV-B wavelengths. This result showed that the protection of lens A was higher. It is seen that the UV transmittance taken with the phocometer is 45% UV in A lens and 91% UV in B lens. The results obtained by UV/VIS spectrophotometer and phocometer supported each other. The results will contribute to the literature by revealing the importance of UV-protected monomer-containing contact lenses in vision equipment, and by enabling the development and selection of full-protection contact lenses.
Measurement of Ultraviolet Light Transmittance of Different Contact Lens Types
Keywords: Nonlinear Optics and Spectroscopy; Doğrusal Olmayan Optik ve Spektroskopi; Atomic; Molecular and Optical Physics (Other); Atomik; Moleküler ve Optik Fizik (Diğer)